2019
DOI: 10.1073/pnas.1814874116
|View full text |Cite
|
Sign up to set email alerts
|

Targeting pericyte–endothelial cell crosstalk by circular RNA-cPWWP2A inhibition aggravates diabetes-induced microvascular dysfunction

Abstract: The crosstalk between vascular pericytes and endothelial cells (ECs) is critical for microvascular stabilization and remodeling; however, the crosstalk is often disrupted by diabetes, leading to severe and even lethal vascular damage. Circular RNAs are a class of endogenous RNAs that regulate several important physiological and pathological processes. Here we show that diabetes-related stress up-regulates cPWWP2A expression in pericytes but not in ECs. In vitro studies show that cPWWP2A directly regulates peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
171
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(172 citation statements)
references
References 31 publications
1
171
0
Order By: Relevance
“…Crosstalk between pericytes and endothelial cells is also mediated by circular RNA. Diabetes-related stress up-regulates a circular RNA, cPWWP2A (PWWP domain containing 2A) expression in pericytes, which inhibit microRNA-579 and regulate vascular integrity (Liu C. et al, 2019).…”
Section: Cross Talk Of Pericytes With Vascular Cells and Glia Endothementioning
confidence: 99%
See 1 more Smart Citation
“…Crosstalk between pericytes and endothelial cells is also mediated by circular RNA. Diabetes-related stress up-regulates a circular RNA, cPWWP2A (PWWP domain containing 2A) expression in pericytes, which inhibit microRNA-579 and regulate vascular integrity (Liu C. et al, 2019).…”
Section: Cross Talk Of Pericytes With Vascular Cells and Glia Endothementioning
confidence: 99%
“…VEGF treatment was also shown to enhance postischemic BBB integrity and reduce infarct volume in rodent models of MCAO (Zheng Gang et al, 2000;Zechariah et al, 2013). Recently, regulating RNA for maintaining the BBB has been investigated and overexpression of cPWWP2A or silencing microRNA-579 expression promoted pericyteendothelial cell crosstalk and microvascular stability (Liu C. et al, 2019). Administration of microRNA-149-5p attenuated BBB permeability and improved the outcomes of rat subjected with transient MCAO (Wan et al, 2018).…”
Section: Prevention Of Bbb Dysfunction Promoting Angiogenesis and Vmentioning
confidence: 99%
“…Further experiments performed by the same authors indicated that cZNF609 silencing decreased retinal vessel loss and suppressed pathological angiogenesis in vivo [66], implying that cZNF609 expression could have diagnostic potential and promising therapy for vascular diseases. More recently, an in vivo study reported that the overexpression of cPWWP2A, a circRNA that acts through miR-579, was able to alleviate diabetes-induced retinal vascular dysfunction [67]. Considering these encouraging preclinical and clinical data, circRNA-based therapy could become a reliable tool in diabetes management.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Research that focuses on these issues along with the development of a multi-markers approach that combines circRNAs and clinical, genetic, epigenetic, and classical markers may help guide medical decision-making in diabetes state and hold great promise especially in terms of precision medicine. ↑ circRNA_15698/miR-185/TGF-β1 axis promoted extracellular matrix (ECM)-related protein synthesis in diabetic nephropathy progression [71] Gestational Diabetes circ_5824, circ_3636, circ_0395 ↓ Suspected to be involved in the occurrence and pathogenesis of GDM [79] hsa-circRNA_0054633 ↑ Change in its expression in the placental villi of GDM patients may reflect its potential role in the development of GDM [78] Diabetic Retinopathy circRNA-0005015 ↑ Involved in diabetes retinopathy by acting as miR-519d-3p sponge to increase the expression of its target genes, MMP-2, XIAP, and STAT3 [64] circRNA-HIPK3 ↑ Promotes retinal vascular disorders by blocking miR-30a-3p members function to reverse the expression of their target genes VEGF, FZD4, and WNT2 [65] cZNF609 ↑ Role in mediating vascular dysfunction by acting as miR-615-5p sponge [66] circRNA-cPWWP2A ↑ Alleviates diabetes mellitus-induced retinal vascular dysfunction by sponging miR-579 [67] Abbreviations: CVD, cardiovascular disease; FZD4, frizzled class receptor 4; GDM, gestational diabetes mellitus; MYRIP, myosin VIIA and Rab interacting protein; MMP-2, matrix metalloproteinase-2; PAX6, the paired box gene 6; SLC2A2, solute carrier family 2 member 2; STAT3, signal transducer and activator of transcription 3; TGF-β, transforming growth factor-beta; VEGF, vascular endothelial growth factor; T2DM, type 2 diabetes mellitus; VSMCs, vascular smooth muscle cells; WNT2, Wingless-type MMTV integration site family, member 2; XIAP, X-linked inhibitor of apoptosis protein; ↑, up-regulated; ↓, down-regulated.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…For example, the lncRNA PVT1 is up-regulated in RB tissues and silencing PVT1 can suppress the tumor growth (Wu et al, 2019). Overexpression of circRNA cPWWP2A was reported to alleviate retinal vascular dysfunction in DR by inhibiting miR-579 activity (Liu et al, 2019). miR-27a is up-regulated in uveal melanoma cell lines (Venza et al, 2014) and Sun et al (2009) found that genistein inhibited uveal melanoma cell proliferation in part through decreasing miR-27a expression.…”
Section: Introductionmentioning
confidence: 99%